Improved Functionality, Quality, and Shelf Life of Merguez-Type Camel Sausage Fortified with Spirulina as a Natural Ingredient - Djamel Djenane; Boumediène Méghit Khaled; Yamina Ben Miri; Mohammed Said Metahri; Luis Montañés; Mohammed Aider; Agustín Ariño (Foods)
The objective of the present work was to examine the effect of incorporating spirulina powder (SP) in merguez-type sausages made exclusively with camel meat, as well as to evaluate its physicochemical, microbiological, and sensory quality attributes and its prebiotic potential. The final purpose was to offer an innovative meat product to increase camel meat consumption. Several innovative fresh sausage formulations were developed using SP (00, 100, 250, and 500 mg/kg) and stored under vacuum conditions with refrigeration at 1 ± 1 °C for 35 days. A control group of camel sausage without SP was also stored overwrapped (OW) under aerobic conditions, to serve as the negative control. The addition of SP to the vacuum-packed camel sausages extended their shelf life by 20 to 35 days compared to the control group, which was completely spoiled by the fifth day of storage. These results were more pronounced the higher the percentage of SP incorporated into the camel sausage formulation, as indicated by the following parameters: 2-thiobarbituric acid-reactive substances TBARS (1.46 vs. 2.89 mg MDA/kg), CIE a* (14.65 vs. 10.12), total volatile basic nitrogen TVB-N (13.02 vs. 15.09 mg/kg), total psychrotrophic bacteria TPB (5.71 vs. 6.34 log CFU/g), and overall acceptability score (3.17 vs. 2.5). The study of prebiotic potential suggested that the addition of SP to camel sausages promoted the growth of probiotic strains, which in turn were able to inhibit the growth of pathogenic microorganisms such as S. aureus and E. coli O157:H7. In conclusion, this study highlighted how SP, as a clean label ingredient, based on its rich composition and its antioxidant, antibacterial, and prebiotic effects, may represent a source of beneficial substances for human health and offer an alternative approach to producing a new traditional merguez-type sausage with improved acceptance.